Quantitative mapping of nanotwin variants in the bulk. (1st July 2021) - Schultheiß, Jan; Porz, Lukas; Kodumudi Venkataraman, Lalitha; Höfling, Marion; Yildirim, Can; Cook, Phil; Detlefs, Carsten; Gorfman, Semën; Rödel, Jürgen; Simons, Hugh
Abstract: Crystallographic twins are critical to the properties of numerous materials from magnesium alloys to piezoelectrics. Since the onset of the twin formation is highly sensitive to the triaxial mechanical boundary conditions, non-destructive bulk microscopy techniques are required. Elastic strains can be mapped via X-ray diffraction with a 100-200 nm resolution. However, the interplay of strains with nanotwins cannot be characterized. Here, a method based on dark-field X-ray microscopy to quantify the density of nanotwin variants with twin lamellae of sizes as small as several tens of nanometers in embedded subvolumes (70x200x600 nm 3 ) in millimeter-sized samples is introduced. The methodology is corroborated by correlating the local density of twin variants to the long-ranging strain fields for a high-performance piezoelectric material. The method facilitates direct, in situ mapping and quantification of nanoscale structural changes together with their elastic driving fields, which is the key towards controlling and engineering material's performance at nanometric scales. Graphical abstract: Image, graphical abstract